ESIPT-based fluorescence probe for the ratiometric detection of superoxide. (30th January 2019) - Wu, Luling; Liu, Liyuan; Han, Hai-Hao; Tian, Xue; Odyniec, Maria L.; Feng, Lei; Sedgwick, Adam C.; He, Xiao-Peng; Bull, Steven D.; James, Tony D.
Abstract : A simple ESIPT-based fluorescence probe (HMBT-LW ) was developed for the detection of superoxide (O2 ˙ − ). Abstract : A simple ESIPT-based fluorescence probe (HMBT-LW ) was developed for the detection of superoxide (O2 ˙ − ).HMBT-LW was synthesised over two steps and was shown to rapidly detect low concentrations of O2 ˙ − (limit of detection = 7.4 μM), fully reacting within two minutes. Furthermore, HMBT-LW demonstrated excellent selectivity and sensitivity towards O2 ˙ − .